Evaluation of hand injury management at the emergency department – are we getting better? - Nikolić, Jelena; Marinković, Marija; Leković, Dragana; Djozić, Isidora (Vojnosanitetski pregled, 2022)
Background/Aim. Hand injuries are one of the most common injuries seen in emergency departments. Inadequate treatment can lead to prolonged healing, complications, significant morbidity, and serious disability. The aim of this study was to evaluate the epidemiology, risk factors, and treatment of hand injuries in one tertiary care level clinical center. Methods. This study was designed as a descriptive retrospective epidemiological study that involved all patients with hand injuries treated at the University Clinical Center of Vojvodina, Novi Sad, Serbia for seven years. The authors collected sociodemographic and clinical data such as age, gender, mechanism of injury, type of injury, days of hospitalization, type of defect reconstruction, the time of injury, the timing of surgery, and reasons for operative treatment delay. For every hospitalized patient the Modified Hand Injury Severity Score (MHISS) was calculated. All data were analyzed using SPSS IBM 21.0 software. Results. From 2012 to 2018, 34,796 patients were treated for hand injury at the University Clinical Center of Vojvodina, with 554 (1.6%) hospitalized patients. The mean age of patients was 43.2 years; the majority of them (87.55%) were men, and most (47.2%) were injured at home. Most injuries occurred during knife handling. The average length of stay for hospitalized patients was 4 days. MHISS score for most patients was over 50 and was classified as severe. It was noticed that the waiting time for operation became shorter throughout the selected years. Conclusion. Hand injuries present a complex problem that can sometimes be underestimated by patients. The requirement of highly specialized hand surgeons, sometimes special equipment (e.g., microscope), multiple operations, prolonged rehabilitation, possible invalidity, and high cost of treatment calls for careful evaluation of the problem and the development of proper strategies in order to be able to lower the costs and obtain better medical care for all people with higher injury risk.